Protocol for preparing Drosophila genomic DNA to create chromosome-level de novo genome assemblies - Alexis L. Sperling; Daniel K. Fabian; Erik Garrison; David M. Glover (STAR Protocols, 2024)
Summary: De novo genome assemblies are common tools for examining novel biological phenomena in non-model organisms. Here, we present a protocol for preparing Drosophila genomic DNA to create chromosome-level de novo genome assemblies. We describe steps for high-molecular-weight DNA preparation with phenol or Genomic-tips, quality control, long-read nanopore sequencing, short-read DNA library preparation, and sequencing. We then detail procedures of genome assembly, annotation, and assessment that can be used for downstream comparison and functional analysis.For complete details on the use and execution of this protocol, please refer to Sperling et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.